Beyond the Tourist Gaze: Mobility, Identity, and Freedom in Manjushree Thapa’s Seasons of Flight - Acharya, Usha (Literary Studies, 2026)
Travel literature often depicts journeys as leisurely and self-discovering adventures. In contrast, Manjushree Thapa’s Seasons of Flight unveils migration as an economic necessity that also leads to freedom. The protagonist, Prema, experiences difficulties in balancing her Nepali roots with her new life in the United States, revealing travel as a means of both escape and adaptation. This paper explores how her journey challenges societal expectations, reinterprets mobility as a feminist act, and blurs the distinctions between migration and tourism. Drawing on critical concepts of “mobility justice” by Mimi Sheller, “feminist geography” by Doreen Massey, and “transnational identity” by Stuart Hall, this study attempts to explore how migration redefines traditional travel narratives by emphasizing gender, survival, and cultural blending.